Energy-absorption buildup factors and specific absorbed fractions of energy for bioactive glasses - Sayyed, M. I.; Manjunatha, H. C.; Gaikwad, D. K.; Obaid, Shamsan S.; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin (National Institute R and D of Materials Physics, 2018)
In the present work, effective atomic numbers Zeff, energy-absorption buildup factors EABF and specific absorbed fractions of energy (Φ) for different bioactive glasses have been calculated in the present work. Geometric-Progression (G-P) fitting method was used for computation of EABF. The computed EABF is used to estimate the values of Φ. It is shown that the EABF and Φ are dependent on Zeff and mean free path. In addition, EABF and Φ were the largest for S4 and S7.The results in this work could be useful in choosing a suitable type of these glasses which in turn are able to resist possible radiation damages at human body and to determine the thickness and shape of the bioactive glasses needed.